2019
DOI: 10.2478/jee-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Direct currents in power transformers

Abstract: The article is devoted to the physical nature of geomagnetism, magnetic storms and methods of predicting their origin and deals with geomagnetic induced currents called GIC (Geomagnetically Induced Currents) and their effect on power transformers. A simplified, single-phase transmission system is described mathematically and its analysis was performed. Also the phenomenon of periodic semi-saturation of the magnetic circuit of the transformers resulting in current overload of the transformer windings, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Core and winding heating caused by the induced current , and short-circuit phenomenon may lead to mechanical damage problems, and the reduced working efficiency of the heat sink will also lead to local overheating of the transformer. Based on this, it is necessary to study the effect of coating on the thermal performance of the transformer objects.…”
Section: Resultsmentioning
confidence: 99%
“…Core and winding heating caused by the induced current , and short-circuit phenomenon may lead to mechanical damage problems, and the reduced working efficiency of the heat sink will also lead to local overheating of the transformer. Based on this, it is necessary to study the effect of coating on the thermal performance of the transformer objects.…”
Section: Resultsmentioning
confidence: 99%
“…If a magnetic storm then arrives in the area of the transmission system, we can measure the GIC directly on the VHV conductors [3,4]. For example, works [5][6][7][8][9][10][11] deal with the calculation of the size of the GIC in the VHV line. Measurements on 400 kV lines showed that in England the GIC reached a value of 10 to 15 A, while in the Nordic countries up to 200 A, with a duration of up to several tens of minutes [12,13].…”
Section: Geomagnetic Induced Currents In Power Transformersmentioning
confidence: 99%
“…This phenomenon is called semisaturation of magnetic circuits. The theoretical solution [13] and the investigation of faults in practice [7] to [16] show that the current overload can range from 2.5 times to three times the nominal value. Example.…”
Section: Figure 2: Simple Model Of Transmission Systém: 1 -Generator ...mentioning
confidence: 99%